Storytelling and management. - Zungu, Nkosenhle H (My University, 1995)
The concept of storytelling and management / organisation throughout the World has been intensively researched in recent years. For instance, Blunt and Jones, 1991; Lessem, 1989, 1993, 1994; Christie, 1993; Chown, 1994; Mbigi, 1993; Zemke, 1990; O'Reilly. 1985; Wilkins, 1984 and many more, have made a significant contribution towards storytelling and management. This report was aimed at providing a partial answer to the following question: "At the level of management style or in their technique, are South African managers inspired storytellers or detached analysts?" The fundamental aim was to establish whether storytelling forms an important part of the South African manager' s leadership repertoire. In conjunction with this aim, the proposition made by Lessem (1994) that storytelling competence is an important subset of communal management, was tested. Propositions for this research were as follows: Storytelling is an important competency for South African managers. • Storytelling is used consciously by South African managers to achieve specific aims. • South African managers can identify the characteristics of good, healthy stories and good storytellers in organisations. • South African managers can identify specific examples ·of stories used in their own organisations. • South African managers can identify other managers who use storytelling as part of their leadership repertoire. The research was confined to organisations operating within the PWV boundaries. the method of "snowball" sampling was utilised to collect the data, whereby telephonic contact was made with individual members of' executive teams in organisations. These individual managers were asked if they could identify any persons within the executive team whom they would characterise as using stories as part of their leadership repertoire. (Abbreviation abstract)
A research report submitted to the Faculty of Business Administration, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for Degree of Master of Management.
Keywords: Communication in management.; Management -- Africa.; Communication In Organizations